2012
DOI: 10.1093/hmg/dds448
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation improves the outcome of Atm-deficient mice through the migration of ATM-competent cells

Abstract: Ataxia telangiectasia (A-T) is a highly pleiotropic disorder. Patients suffer from progressive neurodegeneration, severe bronchial complications, immunodeficiency, hypersensitivity to radiotherapy and elevated risk of malignancies. Leukemia and lymphoma, along with lung failure, are the main causes of morbidity and mortality in A-T patients. At present, no effective therapy for A-T exists. One promising therapeutic approach is bone marrow transplantation (BMT) that is already used as a curative therapy for oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 55 publications
5
35
0
Order By: Relevance
“…7 At the face of Purkinje cell loss and progressive lung destruction several studies have shown that BMDC are able to contribute to neogenesis of cerebellar Purkinje neurons or lung tissue regeneration and protection which is of special interest for a therapeutic approach for A-T. 8,9 In Atm-deficient mice, BMT significantly inhibited tumorigenesis and improved the immunity, weight gain and fitness. 10,11 Our results further showed the migration of CD31 +CD45-endothelial cells and EpCAM+ epithelial cells into the lung tissue of transplanted Atm-deficient mice. 10 However, BMT using a non-myeloablative host-conditioning regimen with cyclophosphamide (CP) and anti-thymocyte globulin did not result in full donor chimerism.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…7 At the face of Purkinje cell loss and progressive lung destruction several studies have shown that BMDC are able to contribute to neogenesis of cerebellar Purkinje neurons or lung tissue regeneration and protection which is of special interest for a therapeutic approach for A-T. 8,9 In Atm-deficient mice, BMT significantly inhibited tumorigenesis and improved the immunity, weight gain and fitness. 10,11 Our results further showed the migration of CD31 +CD45-endothelial cells and EpCAM+ epithelial cells into the lung tissue of transplanted Atm-deficient mice. 10 However, BMT using a non-myeloablative host-conditioning regimen with cyclophosphamide (CP) and anti-thymocyte globulin did not result in full donor chimerism.…”
Section: Introductionsupporting
confidence: 64%
“…10,11 Our results further showed the migration of CD31 +CD45-endothelial cells and EpCAM+ epithelial cells into the lung tissue of transplanted Atm-deficient mice. 10 However, BMT using a non-myeloablative host-conditioning regimen with cyclophosphamide (CP) and anti-thymocyte globulin did not result in full donor chimerism. In addition, the engraftment of donor-derived cells into the lung tissue was low and no cells migrated into the cerebellum.…”
Section: Introductionsupporting
confidence: 64%
See 2 more Smart Citations
“…DSBs activate ATM (Ataxia-Telangiectasia mutated) and ATR (ataxia telangiectasia and Rad3) kinases which phosphorylate as many as 700 proteins that transduce the DNA damage signal, arrest the cell cycle and start DNA repair or, if the damage cannot be repaired, activate apoptosis [2,3]. Unlike most other DNA damage, DNA DSBs directly threaten genomic integrity; thus, these repair processes are essential for preserving genomic structure, and reducing mutagenic risk and oncogenesis.…”
Section: Argument For and Against Conditioningmentioning
confidence: 99%